The Representation of Women in Post #MeToo Hollywood: Three Case Studies – Bombshell, The Assistant and Once Upon a Time… In Hollywood - Berraf, Hana Lina Dalel (AMERICANA E-journal of American Studies in Hungary, 2022)
This article explores the representation of women in three Hollywood movies, namely Jay Roach’s Bombshell, Kitty Green’s The Assistant and Quentin Tarantino’s Once Upon A Time… In Hollywood, released in 2019. The aim behind this analysis is to explain these movies’ different approaches to the representation of women as well as how the various types of discourse being circulated by each of them is influenced by the writers and directors’ personal ideologies. Additionally, through this analysis, the relation between the Me Too movement and the American film industry will be drawn. To do so, both new historicism and feminist film theory will be combined to form the theoretical framework based on which the primary sources will be analyzed